Analysis of the ultimate water resources carrying capacity in Yancheng, China - Zengchuan Dong (IWA Publishing, 2021)
Unreasonable development and utilization of resources has caused serious environmental problems, especially water shortage and water pollution. Determining the largest population size and economic scale that water resources can support without destroying the ecological environment in a region, that is, ultimate water resources carrying capacity (UWRCC), helps to realize the sustainable utilization of water resources. UWRCC is a variable value which is easily affected by natural conditions, technical level and economic status. This study proposes a UWRCC research method that combines multi-objective optimization and scenario analysis. This method draws a diagram of UWRCC result sets based on multi-scenario UWRCC calculation, through which UWRCC values under different specific technical and economic levels are easily and quickly obtained. This method has been applied to Yancheng in this study and the quantitative relationship between technical level, economic level and UWRCC of Yancheng was analyzed. Taking Yancheng as the research area, this study analyzes the quantitative relationship between the technical level, economic level and UWRCC of Yancheng. The results show that according to existing government planning, Yancheng's water resources will be sufficient to support socioeconomic development. But the districts of Yandu, Tinghu, and Binghai will experience population and gross domestic product overloading in future years. In addition, a diagram of the UWRCC sets of Yancheng was obtained and it provides a reference for local water resources management. HIGHLIGHTS The characteristic indicators of ultimate water resources carrying capacity (UWRCC) are population and economic scale.; A new analysis method of UWRCC is proposed.; The UWRCC under different technical and economic levels of Yancheng were calculated.; A diagram of the UWRCC result sets of Yancheng was drawn.; Yancheng's water resources will be sufficient to support development in the future.;